Exercise of Civil-Law Rights: Categories in the Context of Their Digitalization - V. L. Volfson (Теоретическая и прикладная юриспруденция)
With digital rights designated to the objects of civil rights in Art. 128 of the Civil Code, Art. 141.1 amended to include their legal definition, and a new wording of Art. 309 introducing ‘smart contracts’, the digital reform recently enacted in the Russian civil law has seen some major novelties. Needless to say, these accomplishments have challenged Russian civil law theorists. Discussions are underway to resolve both doctrinal and applied issues that had been more than obvious well before the legislative move which, according to one of the opinions, was an ‘admissible’ experiment. What remains now is to assess its viability. The author of this work set the goal to explore the way digital rights, primarily those that arise from ‘smart-contracts’, are (or can be) ‘exercised’. This is a perspective where a fundamental gap between ‘smart-contract’ and civil contract emerges. In the author’s view, efforts to overcome it by expanding the concept of subjective rights and the principles of contract law will not succeed. Since no proper verification of the interests of the parties to ‘smart contracts’, which are essentially a computer code, is available, and as the same refers to linguistic verification of their will, there is no way for ‘smart contracts’ to enter the domain of law. Digital ‘contracts’ are unapt to honour the principle of contractual equilibrium. The ‘self-execution’ of these contracts, as well as their inherent inability to be violated, are, if put in the civilistic context, their fatal flaw, and by no means a virtue. The article also shows that though instruments to ensure a relative irreversibility of rights are not unfamiliar to private law, they cannot serve as an excuse for such regime in contract obligations. That fixation of rights and transactions in digital form has become fully enshrined in the civil law is arguably the only compatible with its principles as well as much anticipated impact the digital reform has brought about.